PEMBERDAYAAN LANSIA DALAM PENINGKATAN MUTU KESEHATAN DENGAN PROGRAM SENAM LANSIA DI DESA SIBANGKUA ANGKOLA BARAT - Harahap, Hasni Yaturramadhan (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2021)
Empowerment of the elderly in improving health with the Elderly Gymnastics Program in Sibangkua Village can start through the role of the Elderly Posyandu for KKN Students at Aufa Royhan University in Padangsidimpuan City Group I. Posyandu activities encourage the empowerment of the elderly to increase health awareness. used to determine the level of health in the elderly. Elderly gymnastics is one of the sports that can be done regularly so that the elderly's fitness is increasing. The purpose of this study was to determine the effect of elderly exercise on the fitness of the elderly in the elderly posyandu. The aims of this study were to 1) describe the elderly posyandu program; 2) identify the health of the elderly in Sibangkua Village; 3) analyze the achievement of the principle of empowerment; 4) and analyze the impact and response of the community regarding the Elderly Gymnastics Program. The data collection method in this study was obtained through observation, interviews, documentation studies, and fieldwork. The results showed that the empowerment program for the elderly in improving health through the Elderly Gymnastics program for Students of the Aufa Royhan University in Padangsidimpuan City Group I included health checks, elderly gymnastics, as well as health socialization and counseling about the importance of Elderly Gymnastics for health. The program plays a role in improving the health condition of the elderly which can be said to be in good health and there are no complaints of serious illnesses, only a few elderly have complaints of illness. The implementation of the empowerment principle has also been achieved in an effort to empower the health of the elderly. The impact obtained from the Posyandu program for KKN Students at Aufa Royhan University in Padangsidimpuan City Group I is that respondents become more aware of health problems so that they pay more attention to their daily lifestyle. The role of the Posyandu for KKN Students at Aufa Royhan University in Padangsidimpuan City Group I in empowering the health of the elderly also received a good response from the community. Keywords:Elderly Posyandu, Community, elderly gymnastics